External Supply Chain Management factors and Social Performance in Thai Manufacturing Industry: Moderating Role of Green Human Resource Practices - Waleerak Sittisom; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
The prime concern of present study is to explore the dimension of sustainable performance by evaluating the relationships with external green supply chain actors. The study addresses an important dimension of sustainable performance known as social performance, the objectives of the study entails to explain the relationship between external green supply chain factors including environmental cooperation and reverse logistics. The green aspect of supply chain has gained attention of various research scholars and practitioners to explore the influence on various organizational performance related outcomes. The present study addresses the relationship between dimensions of green supply chain management and social performance with moderating role of green human resource management, greening aspect of HR entails basic functions of HR including green hiring, green training and development and green performance and compensation management. The results of the study demonstrates that there is positive and significant relationship between environmental cooperation and social performance of manufacturing firms of Thailand, hypothesis H1 accepted on statistical grounds. The relationship between reverse logistics and social performance was also found to be positive and significant on the base of statistical grounds, further, study examined the moderating role of green HR practices between the relationships of constructs, the hypothesis H3 moderating effect between environmental cooperation and social performance was found significantly positive on the base of statistical grounds, but hypothesis H4 was rejected on statistical grounds as no moderating effect was examined between the relationship of reverse logistics and social performance.